Teaching requesting skills to non-verbal children with down syndrome through a picture-based intervention - Galindo, Shari Ann Katlin C.; Echavia, Darlene D.; Magtoto, Frances Olivia M.; Olegario, Lizamarie Campoamor (Quezon City College of Education, University of the Philippines Diliman, 2019)
This study focused on teaching requesting skills to non-verbal children with Down Syndrome (NVCDS) through a picture-based intervention (PBI). The PBI was developed by the researcher as an alternate and functional method for requesting that is not limited to gestures and that would allow the NVCDS to request for specific objects in a more intelligible manner. The participants were comprised of five NVCDS with a developmental age of 7-10 years-old. The picture-tool which consisted of 12 pictures: (1) three pictures of coloring tools; (2) three pictures of snack items; (3) three pictures of drinks, (4) three pictures of toys. Sets of selected pictures were presented using teaching strategies that were proven to be effective in teaching concepts. The NVCDS were taught to choose and pick-up the picture of his or her desired item and exchange the picture for the corresponding item with a communicative partner. Each participant underwent 14 intervention sessions. The findings of the study were presented using a case study method. The study found that prior to the intervention, the five NVCDS made use of pointing and reaching gestures when requesting. During the intervention, it was noted that the NVCDS responded positively to the PBI. Three NVCDS responded consistently as the sessions have progressed, whereas two NVCDS needed more practice and training. The type of activity, the materials, and the process of teaching were found to have positive contributions to the response of the NVCDS during the PBI. Further, the parents and guardian of the NVCDS reported that the picture-tool was helpful in facilitating the requesting skills of the NVCDS. However, the long-term effect of the PBI was not established. It was found that the parents and guardian were not able to use the picture-tool as natural as possible in the home setting.
Thesis
Includes bibliographical references.
Keywords: Down syndrome -- Patients -- Education; Language disorders in children; Speech disorders in children; Picture-based intervention